Accessibility of young adolescents to information on dentai caries in Ibadan, Nigeria (2019)
The prevalence of dental caries, which is on the rise among adolescents in Nigeria has been associated with poor oral health awareness. It remains unknown if information about dental caries is available to young adolescents. This study therefore, determined the accessibility of young adolescents to information on dental caries in Ibadan, Nigeria. A cross sectional study was conducted among 911 pupils aged 10 to 12 years in 12 randomly selected public primary schools in three Local Government Areas in the metropolis of Ibadan. Data were obtained with structured interviewer administered questionnaires. Data obtained was analysed using SPSS version 23. Statistical significance was set at p < 5%. Only 90 (9.9%) pupils had accessed information on dental caries prior to the interview. Information on dental caries were accessed through dentists, 66 (73.3%) and school teachers 24 (26.7%). Pupils who were males (OR = 1.7, CI = 1.0 - 2.7, p = 0.04), whose parents had tertiary education (OR = 3.4, CI = 1.7 - 6.8, p < 0.001), had consulted a dentist (OR = 6.0, CI = 3.5 - 10.6, p < 0.001), rated their oral health as poor (OR = 2.0. CI = 1.1 -3.5, P = 0.024) or perceived a need for dental treatment (OR = 1.5, CI = 0.8 - 2.7, p = 0.196) were more likely to have accessed information on dental caries previously. Very few pupils had prior access to information on dental caries and dentists were the major sources. Male gender, higher parental education, previous dental consultations and poor self-rating of oral health were significant predictors of prior access to information on dental caries